Analysis of Damage to Localizer Equipment (Case Study of Sultan Iskandar Muda Airport, Banda Aceh) - Asri Santosa; Mutiara Widasari Sitopu; Donna N. M Sirait; Darmeli Nasution (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
In the world of aviation, localizer equipment is an important piece of equipment is important in the instrument landing system. If the localizer equipment is damaged, it will disrupt the flight process that occurs at the airport. For this reason, to keep the localizer equipment in optimal condition, the technicians must always check the condition of the equipment so that it is always in good condition when it is run. If the localizer equipment is damaged, the technician must quickly where the damage to the equipment is. The process of checking the condition of the connected RS232 DB9 serial cable, and checking the voltage on the serial port on the LCP module. If the RS232 DB9 serial cable is damaged or disconnected, you must replace the RS232 cable, then when checking the voltage of the LCP module serial port, the voltage on the LCP port must match the standard, which is 8 V if the voltage drops, the LCP module must be replaced immediately.